Pengembangan Modul Berbasis Cognitive Load Theory dan Worked Example untuk Memfasilitasi Berpikir Kritis Siswa Kelas VII - Elsa Mayasari Longkun; Majid; Bertu Rianto Takaendengan (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to develop a mathematics teaching module based on Cognitive Load Theory using the Worked Example approach to facilitate the critical thinking skills of seventh-grade students at SMP Negeri 2 Satap Tilongkabila in the area of data presentation. This study was motivated by students’ low critical thinking skills, the limited availability of innovative teaching materials, and the high level of extrinsic cognitive load in mathematics learning. The research method used was research and development (R&D) employing the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The product developed is a teaching module designed based on the principles of Cognitive Load Theory, such as content segmentation, reduction of the split-attention effect, and the systematic use of tiered worked examples. The research results indicate that the developed module meets the criteria for high validity based on subject matter expert validation at 87% and is valid based on media expert validation at 72%, as well as highly practical based on teacher feedback at 98%. Additionally, student feedback on the module’s use achieved an 86% positive rating, categorized as very positive, indicating that the module is easy to understand, engaging to use, enhances learning motivation, and helps students grasp concepts in a more structured manner. This module also helps reduce unnecessary cognitive load and fosters students' critical thinking skills through activities that involve analyzing, evaluating, and drawing conclusions in the mathematics learning process.